Ligularia amplexicaulis (wall.) DC. Essential oil composition and antibacterial activity. Issue 3 (4th May 2018) - Joshi, Deepshikha; Nailwal, Manoj; Mohan, Lalit; Melkani, Anand B.
Abstract: The essential oil samples from the aerial parts of Ligularia amplexicaulis (wall.) DC. growing wild in the Himalayan region of Uttarakhand, India were isolated by steam distillation and analysed by capillary GC-FID and GC/MS. The oil samples were extracted and analysed separately from the plant material collected from two different locations (Tungnath and Munsiyari, Uttarakhand, India). The oil samples showed quantitative variation with respect to major constituents. Both the oil samples were rich in monoterpene hydrocarbons (67.3 and 82.4%, respectively). Total 47 compounds were identified with limonene (34.0 and 22.0%), p -cymen-8-ol (16.0 and 8.0%), α -pinene (12.0 and 10.0%) and p -cymene (9.0 and 37.0%), respectively, as the major constituents. The oil showed significant antibacterial activity against Gram-negative bacteria Escherichia coli, Agrobacterium tumefaciens, Klebsiella pneumoniae, Xanthomonas phaseoli, Salmonella enteric enterica and Gram-positive Bacillus subtilis, Staphylococcus aureus, Enterococcus faecalis . Minimum inhibitory concentration value (31.25 μL/mL) was observed against B. subtilis, S. aureus, E. faecalis, E. coli, A. tumefaciens and P. multocida .